Analisa Faktor-Faktor Penentu Efesiensi Biaya Bank Umum Syariah Indonesia Menggunakan Metode Parametrik Periode 2017-2021 - Adela Putri, Sania; Yafiz, Muhammad; Syarvina, Wahyu (JOVISHE : Journal of Visionary Sharia Economy, 2022)
This study aims to measure the efficiency level of Indonesian Islamic Commoercial Banks in 2017-2021 using the cost function using the parametric Stochastic Frontier Approach (SFA) method and analyse the influence of the component variables forming the efficiency level of Indonesian Islamic Commercial Bank in 2017-2021using the cost function with the method OLS parametric regression. The research method used is a quantitative research method. The samples in this study were Bank BCA Syariah and Bank Victoria Syariah.The result of this study indicate the the average throughout the research period (2017-2021) the efficiency level of costs, Bank Victoria Syariah and Bank BCA Syariah, is 1973803.5 and 77701744.8 respectively, where this efficiency level is included in the efficiency category. Then the determinants of the component variables forming the cost function with the OLS regression method at the two banks have differences. Bank BCA Syariah is significantly influenced by three of the four component variables on costs while Bank Victoria has no significant effect on the four components on costs.